Public History Meets Humanitarian Communication: The Visual Politics and Narratives of Red Cross Museums in Europe and the United States, 1920s to 2010s - Sönke Kunkel (Journal of Humanitarian Affairs, 2021)
Interpreting Red Cross museums as a visual medium, this essay explores the visual politics of Red Cross museums through the twentieth century. The essay puts particular emphasis on the entanglements between the visual politics and humanitarian narratives of Red Cross museums and identifies three major narratives that museums promoted through the times: a heroic narrative, a narrative of civility, and a volunteer’s narrative. Last, the essay argues that Red Cross museums may offer a fruitful field to encourage more engagement between (public) historians and humanitarian practitioners.